The Legal Validity Of Reading A Notary Deed In Front Of The Confronter Via Video Conference - Husnul Amirah, Anggi (Universitas Islam Malang, 2023)
Abstract : Notaries are required to read the contents of the deed to ensure that the parties know all relevant information and clear its contents. Article 16 of the UUJN-Amended regulates how notaries should carry out their duties in making authentic deeds. Indonesia is currently in the era of information and communication technology (ICT) which introduces cyberspace (cyberspace, or virtual world) through the internet and allows communication through electronic media that does not require paper. Through this electronic medium, a person will enter a virtual world that is abstract, universal, and does not depend on location and time. Problem Formulation in research How to use electronic systems in making authentic deeds and How is the legal validity of reading deeds by notaries in front of the face through video conference. The research method used is normative juridical with an approach to concepts and laws and regulations. The results of research and discussion show that: First, there is still a lack of laws and regulations governing the use of electronic systems in making deeds, so that in making notarial electronic deeds unreliable, the use of cyber notaries is also not clear enough because the authentic deed itself still conflicts with the requirements of the mechanism in making deeds. Second, the legal validity of reading the deed before the confronter via video conference is considered invalid, because basically it does not have strong legal force and not all technological actions with video conference capabilities can be carried out. If the notary and the parties do not meet the conditions to face off under Article 40 of Law Number 2 of 2014 concerning the Notary Position when reading an authentic deed, then the status of the deed can change which was originally considered authentic and has the strongest evidentiary power to become a deed under hand.Keywords: Reading, Deed, Video Conference.